Capacity for financial decision making in multiple sclerosis. Issue 1 (2nd January 2017) - Tracy, Victoria L.; Basso, Michael R.; Marson, Daniel C.; Combs, Dennis R.; Whiteside, Douglas M.
ABSTRACT: Introduction : Cognitive impairment often occurs in people with multiple sclerosis (MS), and dysfunction involving executive function, new learning, and working memory is especially common. Compromised activities of daily living are linked to this cognitive impairment, and people with MS are apt to be unemployed and struggle to manage domestic responsibilities. Financial decision making is an important activity of daily living, and no study has examined whether it is compromised by neuropsychological dysfunction in people with MS. Method : A battery of neuropsychological tests and a measure of financial decision making (Financial Capacity Instrument, FCI: Marson, D. C. 2001. Loss of financial capacity in dementia: Conceptual and empirical approaches. Aging, Neuropsychology, and Cognition, 8, 164–181) were administered to 50 participants (34 patients with MS and 16 cognitively healthy adults). Based on the neuropsychological test results, 14 patients were classified as having cognitive impairment, and 20 had no significant impairment. Results : The impaired MS patients performed significantly worse than unimpaired patients and the healthy comparison group on most financial tasks. The impaired group retained abilities to count money and display adequate financial judgment. Regression analyses showed that measures of mental flexibility and working memory correlated most strongly with performance on the FCI domains across groups. Conclusions : Cognitively impaired patients with MS have degraded financial skills, which are linked to executive function and working memory deficits.